Pengaruh konsumsi jus wortel terhadap perubahan tekanan darah pada ibu menopause penderita hipertensi di klinik Pratama Hanum Medan - Wardani, Fina Kusuma; Wulan, Mayang; Aisyah, Siti (Journal of Pharmaceutical and Sciences, 2023)
Introduction: Hypertension is one of the most significant causes of mortality in the world, especially in developing countries. Hypertension does not know the age of young or old, but women in menopause are prone to hypertension because estrogen levels decrease. Objective: To ascertain the impact of carrot juice on blood pressure variations in menopausal mothers who suffer from hypertension in the Clinic Pratama Hanum Medan. Method: The study was a quantitative research with Quasy Experimental, One Group Pre-Post Test. The population was 15 Menopause mothers who had hypertension in Hanum Clinic. The sample was 15 people with a mother's menopause. The data analysis is a t-test, then presented as tabulated frequency data. Results of the study, the average blood pressure of postmenopausal women who had hypertension before being given carrot juice was 159.67/92 mmHg. After consuming carrot juice, the mean blood pressure of hypertensive menopausal mothers was measured. 136.67/81.67 mmHg. The results of the Wilcoxon test found that the systolic blood pressure variable obtained a value = 0.001, and diastolic pressure received a p-value = 0.000. The conclusion showed there was an effect of giving carrot juice to change blood pressure in post-menopausal women who experienced hypertension at Hanum Clinic Medan. It is recommended that health workers apply non-pharmacological therapy to reduce hypertension with KIE consumption of carrot juice two times a day with 200 grams of carrots and 250 ml of water.